Unraveling coevolutionary dynamics using ecological genomics. Issue 10 (October 2022) - Amandine, Cornille; Ebert, Dieter; Stukenbrock, Eva; Rodríguez de la Vega, Ricardo C.; Tiffin, Peter; Croll, Daniel; Tellier, Aurélien
Abstract : Coevolutionary interactions, from the delicate co-dependency in mutualistic interactions to the antagonistic relationship of hosts and parasites, are a ubiquitous driver of adaptation. Surprisingly, little is known about the genomic processes underlying coevolution in an ecological context. However, species comprise genetically differentiated populations that interact with temporally variable abiotic and biotic environments. We discuss the recent advances in coevolutionary theory and genomics as well as shortcomings, to identify coevolving genes that take into account this spatial and temporal variability of coevolution, and propose a practical guide to understand the dynamic of coevolution using an ecological genomics lens. Highlights: Coevolution is a fundamental process shaping species interactions and communities. Coevolution has been mostly studied experimentally as an isolated process involving local reciprocal selection between two species. However, species comprise genetically differentiated populations across space in constant interaction with dynamic abiotic and biotic environments. Coevolution is therefore a dynamic equilibrium. The genes and genomic processes underlying the complexity of coevolution over time and space remain poorly known. A range of new theoretical developments, technological advances, and empirical approaches now allow coevolutionary dynamics to be investigated with genomic data from interacting species. Recent advances in population genomics and genome-wide association studies will enable us to better understand the genetic basis of coevolutionary dynamics.